The proliferation markers in patients with different forms of hyperplastic endometrial processes: Markery proliferacji u pacjentek z różnymi postaciami przerostowych procesów endometrium - Krut, Yuri; Zemlyana, Nataly; Gaidai, Natalie; Pavliuchenko, Mykhailo; Amro, Iryna (Journal of Education, Health and Sport, 2022)
Introduction: Endometrial hyperplastic processes (EHP) are characterized by recurrent course, high risk of malignancy, difficulties in diagnosing and predicting the course, which determines their great medical and social significance Objective: To evaluate the levels of proliferation markers Ki-67 and APRIL in serum of women with various forms of endometrial hyperplastic processes (EHP) and their correlation with clinical and anamnestic features. Materials and Methods: The study examined 95 women with endometrial hyperplasia and endometrial adenocarcinoma who underwent treatment in the gynecology department "City Clinical Hospital №7» in Zaporizhzhya and "Zaporozhye Regional Clinical Oncology Center". The first group consisted of 32 women with simple endometrial hyperplasia. The second group included 43 patients with complex endometrial hyperplasia. The third group consisted of 22 women with endometrial adenocarcinoma. Results: The analysis of Ki-67 level revealed an increasing in the patients with simple hyperplasia (p <0.05) and complex hyperplasia of endometrium (p <0.05) compare with control group. The level of the APRIL in serum is increased in group of complex hyperplasia compared with the control group (p <0,05) and simple hyperplasia (p <0,05). Conclusions: Level of APRIL in serum increased in patients with complex endometrial hyperplasia and endometrial adenocarcinoma. Level of Ki-67 in serum was highest in patients with complex endometrial hyperplasia. We found a significant positive association between Ki-67 levels in serum and thickness of M-echo in endometrium, duration of hyperplastic endometrial processes anamnesis, between APRIL in serum and age of patients, duration of hyperplastic endometrial processes anamnesis.